Perbandingan Metode Antrian Paket HTB dan EDCA Untuk Layanan Multimedia Pada WLAN IEEE 802.11n - Taufik Hidayat; Zulfan Zulfan; Munawir Munawir; Susmanto Susmanto (Program Studi Teknik Komputer, Fakultas Teknik. Universitas Serambi Mekkah, 2020)
The development of wireless technology continues to improve quality and increase the speed of data transfer into one important factor that is considered. Each year, wireless technology users continue to increase and communication service needs also experience tremendous traffic surge. The impact of high traffic intensity of data sent can lead to increased data queue and transient transmission network. The problem of network crunch resulting from a high amount of queue data may affect service performance. To get the solution, in this study was tested using Hierarchy Token Bucket (HTB) and Enhanced Distributed Channel Access (EDCA) on 802.11n wireless network. Queuing tests are performed on four types of traffic: voice, video, best effort (BE) and background (BG). Assessment of QoS of HTB and EDCA is based on throughput and delay parameters. The results obtained from throughput testing of the mean value of each data packet, the results show that the EDCA method is better than HTB method. The best throughput results are given on Best Effort(BE) traffic. While on the delay test by using HTB and EDCA method, obtained the average of EDCA delay smaller in multimedia data packet for Video and Voice. In conclusion, the results show that the EDCA method is better than HTB.